If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + -3) = 5(2x + -6) Reorder the terms: -4(-3 + x) = 5(2x + -6) (-3 * -4 + x * -4) = 5(2x + -6) (12 + -4x) = 5(2x + -6) Reorder the terms: 12 + -4x = 5(-6 + 2x) 12 + -4x = (-6 * 5 + 2x * 5) 12 + -4x = (-30 + 10x) Solving 12 + -4x = -30 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + -4x + -10x = -30 + 10x + -10x Combine like terms: -4x + -10x = -14x 12 + -14x = -30 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -14x = -30 + 0 12 + -14x = -30 Add '-12' to each side of the equation. 12 + -12 + -14x = -30 + -12 Combine like terms: 12 + -12 = 0 0 + -14x = -30 + -12 -14x = -30 + -12 Combine like terms: -30 + -12 = -42 -14x = -42 Divide each side by '-14'. x = 3 Simplifying x = 3
| 18=4(y+2)+2 | | 6(x-1)=24 | | x^2+x-252=0 | | 6+8/3=-14 | | 2(3)-7= | | 2a-7= | | 4x-2+6y+y-4= | | -10=-12+4/7n | | -3x=3/4 | | 3(r+3)=6 | | (180-13x)+(6x+17)+67=180 | | 7(k+3)+5=-5(k-3)+17 | | 2/3+x=-13/3 | | 1000=232+2c | | -18=m/8 | | 111-10g=11 | | -2y=24 | | 11-10g=11 | | 9x-9+6x+6=360 | | 28+27k=946 | | y-25=34 | | 2x+4=7x-26 | | 13-7s=20 | | 27-5x=-33 | | 9x-6+x=34 | | 18=-216 | | x/4=-2-3/8 | | 1/2c-10=-4 | | 9x+2x-15=84 | | 4x+16-2x=32 | | 18=3c+12-c+4 | | 4y-6=14y+84 |